2016
DOI: 10.1007/s10616-016-9987-9
|View full text |Cite
|
Sign up to set email alerts
|

Viral IL-10 down-regulates the “MHC-I antigen processing operon” through the NF-κB signaling pathway in nasopharyngeal carcinoma cells

Abstract: The HLA-I antigen processing machinery (APM) plays a crucial role in the anticancer immune response. The loss of surface expression of HLA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…28 In the nucleus, NF-κB bonded to gene promoters in their transcriptional regulatory regions, triggering a sequence of physiological or pathological effects such as an inflammatory response. 46,47 Our previous studies have found that the activation of the NF-κB signaling pathway played an important role in pulmonary toxicity induced by nano NiO. 7 Liu et al 38 reported that nickel sulfate could induce oxidative stress and inflammatory responses in mice liver through TLR4/p38/NF-κB, upregulating the TNF-α and NF-κB protein expression levels.…”
Section: Discussionmentioning
confidence: 98%
“…28 In the nucleus, NF-κB bonded to gene promoters in their transcriptional regulatory regions, triggering a sequence of physiological or pathological effects such as an inflammatory response. 46,47 Our previous studies have found that the activation of the NF-κB signaling pathway played an important role in pulmonary toxicity induced by nano NiO. 7 Liu et al 38 reported that nickel sulfate could induce oxidative stress and inflammatory responses in mice liver through TLR4/p38/NF-κB, upregulating the TNF-α and NF-κB protein expression levels.…”
Section: Discussionmentioning
confidence: 98%
“…Previous evidence showed that NF-κB, a pivotal transcription factor, is a heterodimer consisting of p50 and RelA/p65 subunits. Dysfunction of NF-κB is involved in various diseases [ 34 ]. In nonstimulated cells, NF-κB p65 locates in the cytoplasm where it is bound to its inhibitor protein IκBα; however, the p65 subunit dissociates from the NF-κB p65 complex and translocates to the nucleus in response to cell insults produced by a high glucose concentration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immortalized EVB negative NPC cell lines, CNE1 and CNE2, were kept from the previous research 21. The EVB positive NPC cell line, C666‐1, was obtained from the Cancer Research Institute of Southern Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…The total proteins from different treatments were extracted according to the previously published paper 21. The expression levels of targeted proteins were then measured by Western blot (WB) assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation